THE ANALYSIS OF THE NOISE OF QUANTIZATION OF LINEAR STATIONARY FILTERS OF IMAGE PROCESSING - Nikolay Ivanovich Chervyakov; Pavel Alekseevich Lyakhov; Nikolay Nikolaevich Nagornov (Современная наука и инновации, 2022)
The problem of quantization of the coefficients of arbitrary linear stationary filters in order to minimize the noise of this phenomenon and efficient hardware implementation of digital image processing methods is investigated in the paper. The implementation of the method of linear stationary filtration is proposed, which makes it possible to reduce the number of filter coefficients and simplify the performance of rounding operations.